2021
DOI: 10.24875/acme.m21000187
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children and adults following cardiac surgery for congenital heart disease: A Mexican cohort

Abstract: Objective: The real burden of (congenital heart defects [CHD]) and the improvement after surgical correction or palliation is both reflected in the quality of life (QoL). There are few studies in Latin-America that evaluate QoL in the CHD population. The purpose of this study was to measure the QoL after corrective or palliative surgery for CHD. Materials and methods: An observational, cross-sectional, and comparative study was carried out at the Miguel Hidalgo Centennial Hospital. Patients from 8 to 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Although patients who underwent cardiac surgery have been reported to have poor QoL compared to healthy controls, 32 34 the comparison between CHD patients with and without surgical cardiac intervention seems to be inconclusive. Teixeira et al 22 found that adolescents and young adults who had not undergone surgery had a better QoL both overall and in the physical and social dimensions compared to those who had surgical procedures while Aguilar-Alaniz et al 16 found no significant differences in adolescents. In a longitudinal study, Boukovala et al 35 found that adolescents and adults with CHD reported better physical HRQoL following surgery and catheter intervention compared to the other treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients who underwent cardiac surgery have been reported to have poor QoL compared to healthy controls, 32 34 the comparison between CHD patients with and without surgical cardiac intervention seems to be inconclusive. Teixeira et al 22 found that adolescents and young adults who had not undergone surgery had a better QoL both overall and in the physical and social dimensions compared to those who had surgical procedures while Aguilar-Alaniz et al 16 found no significant differences in adolescents. In a longitudinal study, Boukovala et al 35 found that adolescents and adults with CHD reported better physical HRQoL following surgery and catheter intervention compared to the other treatment options.…”
Section: Discussionmentioning
confidence: 99%
“… 12 14 For instance, using the Pediatric Quality of Life Inventory (PedsQL), a recent study in South India shown a significantly poor median HRQoL total score in healthy compared to CHD patients in children (91.3 vs 80.4), preadolescents (91.3 vs 67.1), and adolescents (89.1 vs 69.6). 13 HRQoL of patients with CHD varies widely across studies and may be dependent on economical, sociodemographic, and medical conditions of patients 15 , 16 and can be used as a good indicator of patient wellbeing and care. Understanding their HRQoL will also help in improving symptom relief and rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Several topics were discussed based on the review of 11 articles, including 5 articles discussing the relationship between quality of life in children with Congenital Heart Disease and healthy or normal children [8,10,12,13,15], 2 articles discussing quality of life in children with CHD according to patient age group [6,11], 3 articles discussing the relationship between quality of life for children with CHD and the type of CHD severity [5,9,14], and 1 article about the relationship between perceived quality of life between children with CHD and caregivers [7].…”
Section: Discussionmentioning
confidence: 99%
“…The review results from one article showed significant results that children with uncorrected CHD had a lower quality of life compared to their healthy peers [8]. The results of the review of two other articles showed that children with CHD who had received treatment had a better quality of life than their healthy peers [12,13]. Meanwhile, the results of the study of the other 2 articles showed that the results of self-reported quality of life scores in children with CHD were comparable or as good as their healthy peers [10,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation